Noninvasive Optical Measurements of Dynamic Cerebral Autoregulation by Inducing Oscillatory Cerebral Hemodynamics - Pham, Thao; Fernandez, Cristianne; Blaney, Giles; Tgavalekos, Kristen; Sassaroli, Angelo; Cai, Xuemei; Bibu, Steve; Kornbluth, Joshua; Fantini, Sergio (Frontiers in Neurology, 2021)
Objective: Cerebral autoregulation limits the variability of cerebral blood flow (CBF) in the presence of systemic arterial blood pressure (ABP) changes. Monitoring cerebral autoregulation is important in the Neurocritical Care Unit (NCCU) to assess cerebral health. Here, our goal is to identify optimal frequency-domain near-infrared spectroscopy (FD-NIRS) parameters and apply a hemodynamic model of coherent hemodynamics spectroscopy (CHS) to assess cerebral autoregulation in healthy adult subjects and NCCU patients. Methods: In five healthy subjects and three NCCU patients, ABP oscillations at a frequency around 0.065 Hz were induced by cyclic inflation-deflation of pneumatic thigh cuffs. Transfer function analysis based on the wavelet transform was performed to measure dynamic relationships between ABP and changes in oxy- (O), deoxy- (D), and total- (T) hemoglobin concentrations measured with different FD-NIRS methods. In healthy subjects, we also obtained the dynamic CBF-ABP relationship using FD-NIRS measurements and the CHS model. In healthy subjects, an interval of hypercapnia was performed to induce cerebral autoregulation impairment. In NCCU patients, the optical measurements of autoregulation were linked to individual clinical diagnoses. Results: In healthy subjects, hypercapnia leads to a more negative phase difference of both O and D oscillations versus ABP oscillations, which are consistent across different FD-NIRS methods and are highly correlated with a more negative phase difference CBF versus ABP. In the NCCU, a less negative phase difference of D versus ABP was observed in one patient as compared to two others, indicating a better autoregulation in that patient. Conclusions: Noninvasive optical measurements of induced phase difference between D and ABP show the strongest sensitivity to cerebral autoregulation. The results from healthy subjects also show that the CHS model, in combination with FD-NIRS measurements, can be applied to measure CBF-ABP dynamics for a more direct measurement of cerebral autoregulation.